Improving Students’ Listening Comprehension through Auditory, Intellectually, and Repetition (AIR) Model Integrated CAKE Application at Grade 11 of SMA Negeri 4 Pematangsiantar - Juni Sari Sianturi; Dumaris Elseria Silalahi; Bobby Pramjit Singh Dhillon (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This research aimed to find out the effect of the Auditory, Intellectually, and Repetition (AIR) Model integrated with the CAKE Application on students’ listening comprehension at grade eleven of SMA Negeri 4 Pematang Siantar. This research used a quantitative method with a quasi-experimental design involving 72 students divided into an experimental class and a control class. The findings showed that the experimental class achieved better improvement than the control class. The result of the t-test showed that the t-observed value (4.37) was higher than the t-table value (2.00). Therefore, the alternative hypothesis (Hₐ) was accepted, indicating that the AIR Model integrated with the CAKE Application had a significant effect on students’ listening comprehension.